Efektivitas Konsumsi Ubi Jalar Rebus dan Jus Pisang dalam Mengontrol Hipertensi pada Ibu Hamil di Puskesmas Bojonggede Tahun 2024 - Ella Nurlaela; Ratna Wulandari; Rita Ayu Yolandia (Lembaga Pengembangan Kinerja Dosen, 2024)
Hypertension in pregnant women is a health issue that needs to be properly addressed to prevent complications. This study aims to compare the effectiveness of consuming boiled sweet potatoes and banana juice in controlling hypertension in pregnant women at Bojonggede Health Center in 2024. The method used was a case study. Respondent 1 was given 300 grams of boiled sweet potatoes and 10 mg of nifedipine for seven days, while Respondent 2 was given 200 ml of banana juice and 10 mg of nifedipine with the same procedure. Blood pressure measurements were taken on the first and seventh days. The results showed that in the boiled sweet potato respondent, blood pressure decreased from 150/100 mmHg to 140/100 mmHg, while in the banana juice respondent, the reduction was more significant, from 150/100 mmHg to 130/90 mmHg. These findings indicate that banana juice is more effective in reducing blood pressure in hypertensive pregnant women compared to boiled sweet potatoes, making it a potential alternative in hypertension management.